Pengaruh Kualitas Produk dan Relationship Marketing Terhadap Kepuasan Konsumen - Miftahul Jannah; Vina Meliana (Research and Community Service UNIVERSITAS KALBIS, 2022)
The purpose of this research to understand the effect of quality product and relationship marketing towards customer satisfaction Ngemil Banana Chips. The data on this research is using quantitative metods with saturated sampling with the criteria that consumed product and as reseller Ngemil Banana Chips. A sample this research is 60 respondents. Multiple regression analysis and hypothesis test which is done by using SPSS 25 is applied as the data technique. The result of this research show that the quality product has effect customer satisfaction with significant score of 0.001 < 0.05, relationship marketing has effect customer satisfaction with significant score of 0.027 < 0.05, and also quality product and relationship marketing simultaneously effect the customer satisfaction with fscore >ftable or 38.514 > 3.16.